Epidemiologic study of patients attended in an Oral Medicine Service between 2014-2016 - Calcia, Thayanne Brasil Barbosa; Antero, Sarah Aparecida Ferreira; das-Chagas, Wagner Pinto; Freire, Nathalia de Almeida; Israel, Mônica Simões; Maciel, Rosemiro de Menezes (Journal of Oral Diagnosis, 2019)
Oral medicine is a dental specialty intended to diagnose current oral diseases, as well as to diagnose and prevent oral manifestations of systemic diseases. This study aimed to evaluate the most commonly diagnosed lesions, as well the main epidemiological cha- racteristics of the patients attended at the oral medicine clinic of São Leopoldo Mandic School - Rio de Janeiro in the period between 2014 and 2016. At the end of the study, a total sample of 175 charts was obtained, whose extracted data were analyzed and plotted. Regarding distribution by gender, we found a major presence of female patients in atten- dance, corresponding to 63% of our sample. Thereafter, greater proportion of patients in the age group of 60 to 69 years was observed in both genres (25 females and 14 males). Considering an ethnic distribution, it was observed that majority of the patients of both genders declared themselves as white-skinned (52 females and 30 males). Among the most diagnosed lesions at the clinic, epithelial pathology was more frequent (n = 23), followed by soft tissue tumors (n = 18), developmental defects (n = 16), bone pathology (n = 14) and dermatological diseases (n = 11). Finally, the percentage of agreement between an initial and a final diagnostic was observed, and among the majorities of the diagnoses, there was a positive correlation (84%). Thus, in this work, the population attended at the clinic consisted, in the majority, of white women between the ages of 40 and 69, with fibrous hyperplasia as most frequent diagnosis. Finally, it is important to point out that the high agreement between an initial hypothesis and the final diagnosis is of utmost importance for excellence in oral medicine attendance, evidencing a quality of the service.